A novel pretreatment method of lignocellulosic material as adsorbent and kinetic study of dye waste adsorption - Ling, Wei Low; Tjoon, Tow Teng; Anees, Ahmad; Norhashimah, Morad; Yee, Shian Wong (Springer Science+Business Media B.V., 2011)
Link to publisher's homepage at http://www.springerlink.com/